2010
DOI: 10.1111/j.1741-3729.2010.00612.x
|View full text |Cite
|
Sign up to set email alerts
|

Financial Arrangements and Relationship Quality in Low‐Income Couples

Abstract: This study explored the association between household financial arrangements and relationship quality using a representative sample of low-income couples with children. We detailed the banking arrangements couples utilize, assessed which factors relate to holding a joint account versus joint and separate, only separate, or no account, and analyzed the association between fiscal practices and men’s and women’s relationship quality. The majority of couples held joint accounts, though over one-quarter also have s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
82
0
5

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(92 citation statements)
references
References 50 publications
(93 reference statements)
5
82
0
5
Order By: Relevance
“…A family unity approach to relationships is characterized by values of family member solidarity, which prioritizes shared goals over individual pursuits, in part through the sharing of family resources (Addo & Sassler, 2010;Bellah et al, 2008). This collectivized approach to financial arrangements is thought to occur under three conditions: 1) exchanges are repeated and continuing; 2) investments in the relationship that cannot be recovered have already taken place; and 3) evaluating repeated exchanges is costly (Treas, 1993;Williamson, 1975).…”
Section: Family Unity Versus Economic Autonomymentioning
confidence: 99%
See 1 more Smart Citation
“…A family unity approach to relationships is characterized by values of family member solidarity, which prioritizes shared goals over individual pursuits, in part through the sharing of family resources (Addo & Sassler, 2010;Bellah et al, 2008). This collectivized approach to financial arrangements is thought to occur under three conditions: 1) exchanges are repeated and continuing; 2) investments in the relationship that cannot be recovered have already taken place; and 3) evaluating repeated exchanges is costly (Treas, 1993;Williamson, 1975).…”
Section: Family Unity Versus Economic Autonomymentioning
confidence: 99%
“…Nevertheless, for theoretical reasons, I included predictor variables that prior literature shows are associated with behavioral differences in the ways people report organizing income within families. These include gender (Pahl, 1995), marital status (Burgoyne & Morison, 1997), parental status (Lyngstad et al, 2011), age (Vogler & Pahl, 1994), race-ethnicity (Addo & Sassler, 2010;Kenney, 2004), education (Treas, 1993), employment status (Kenney, 2006), and income (Copp, Giordano, Manning, & Longmore, 2016). Table 2 shows the means for the sample.…”
Section: Predictor Variablesmentioning
confidence: 99%
“…We are aware of two studies that investigated the association between shared financial values (assessed as couples who had joint versus separate bank account) and relationship satisfaction (Addo & Sassler, 2010;Steuber & Paik, 2014). Both studies found that participants who pooled their finances reported a higher relationship satisfaction than did those who did not.…”
Section: Shared Financial Valuesmentioning
confidence: 99%
“…Essa categoria integrou estudos que: (1) Examinou associações entre renda, assistência governamental e qualidade conjugal (Schramm & Harris, 2011). Os resultados revelaram que quanto menor a renda conjugal, maior o auxílio governamental e menor a qualidade do relacionamento e o comprometimento dos casais; (2) Avaliou a associação entre acordos fi nanceiros domésticos e qualidade conjugal (Addo & Sassler, 2010). Os resultados evidenciaram que contas conjuntas foram associadas a maiores níveis de qualidade conjugal e que acordos individualistas alteraram a qualidade conjugal de mulheres, estando associados à redução de sentimentos de intimidade, compatibilidade sexual e satisfação com a resolução de confl itos; (3) Analisou a relação entre recursos econômi-cos e qualidade da relação entre casais jovens (Halliday Hardie & Lucas, 2010) e foi verifi cado que difi culdades econômicas estavam associadas à maior número de confl itos conjugais, tanto em casais casados quanto em casais coabitantes.…”
Section: Etapaunclassified